GASP – XVI. Does cosmic web enhancement turn on star formation in galaxies?. Issue 2 (21st May 2019) - Vulcani, Benedetta; Poggianti, Bianca M; Moretti, Alessia; Gullieuszik, Marco; Fritz, Jacopo; Franchetto, Andrea; Fasano, Giovanni; Bettoni, Daniela; Jaffé, Yara L
Abstract: Galaxy filaments are a peculiar environment, and their impact on the galaxy properties is still controversial. Exploiting the data from the GAs Stripping Phenomena in galaxies with MUSE, we provide the first characterization of the spatially resolved properties of galaxies embedded in filaments in the local Universe. The four galaxies we focus on show peculiar ionized gas distributions: H α clouds have been observed beyond four times the effective radius. The gas kinematics, metallicity map, and the ratios of emission-line fluxes confirm that they do belong to the galaxy gas disc; the analysis of their spectra shows that very weak stellar continuum is associated with them. Similarly, the star formation history and luminosity weighted age maps point to a recent formation of such clouds. The clouds are powered by star formation, and are characterized by intermediate values of dust absorption. We hypothesize a scenario in which the observed features are due to 'Cosmic Web Enhancement': we are most likely witnessing galaxies passing through or flowing within filaments that assist the gas cooling and increase the extent of the star formation in the densest regions in the circumgalactic gas. Targeted simulations are mandatory to better understand this phenomenon.